Identitet og litteraturhistorie - Mai, Anne-Marie (Versita, 2012)
The paper discusses the need for a renewal of literary historiography and presents different strategies for new historical readings that can generate interest in older literature. Students at the Danish universities and high schools are supposed to have a solid knowledge of literary classics and the methods of historical reading. In a Danish context the school's task to form and develop young people have been linked to the experience of reading literature and knowing literary history. But the older literature seems to have become a compulsory reading which students want over with as quickly as possible. It is a big problem since the European post-national societies require a historical understanding of cultural values and the sources of these values. Literature gives the readers the opportunity to see and interpret themselves in relation to their surroundings, to meet the strange and unknown and to empathize with other people's thoughts and ideas. Literature creates a special feeling of language and an understanding of how linguistic meaning is formed. The paper presents discussions of literary historiography and new approaches to literary history.
Identity and Literary History
Keywords: Literary historiograhy; education; New approaches to literary history; Cultural values of post-national Europe; Litteraturhistorieskrivning; Undervisning; Nye tilgange til litteraturhistorie; Kulturelle værdier af det postnationale Europa